Ensuring the sustainability of public sector utility projects in Pakistan - Sohail, Shahid (2008)
Pakistan is a developing country having a large imbalance between its resources and needs. Any Government that is at the helm of affairs always finds its reputation at stake due to the overwhelming expectations of its population, which it cannot fulfill completely as such, has to find other means that would keep them going peacefully. One of the steps she takes is the initiation of the public sector development projects and ensuring their completion within their incumbency. This gives them a public strength and makes them politically healthy because more the Projects are there on ones credit the greater is the politician / leader thought to be. Unfortunately, once such projects are completed, either very little or no efforts are made to ensure their sustainability, which results into under drawl of the benefits of the project. This situation gets graver for those projects whose ultimate resultant is a utility service because such projects require extensive effort for deriving the conceived benefits. Planning and Development Division of the Government, although remains concerned about the benefits of the Projects and severely monitors the Projects till their completion, but lacks firm control towards ensuring their sustainability by leaving everything to the sponsoring agency, who do not take the desired care that results into under drawl of its benefits. Several reasons can be attributed to this lack of effort by the sponsoring agency; however, this can be overcome by keeping stringent control at the Project Initiation stage. As such, the Project Charter, which forms the basis of initiation of the Projects, is required to be elaborated for the Projects of utility services to be undertaken in the developing countries. In this paper, the comparison is drawn between project life cycles conceived by august project management bodies of knowledge and compared with those in practice with the Government of Pakistan. The suggestions for increasing the possibilities of ensuring the sustainability of public sector projects shall also be made.